Hungry for change : reducing food waste among youths in Singapore - Heng, Jian Siong (2017)
Hungry for Change is a behaviour change communication campaign calling for a reduction in food waste behaviours among youths when dining out. Led by four final-year undergraduates from the Wee Kim Wee School of Communication and Information at Nanyang Technological University (NTU), Hungry for Change targeted youths aged 17 to 25 years old studying in local polytechnics and universities, encouraging them to practise the food waste reduction behaviour of asking for smaller portions so as to minimise the amount of food they waste when dining in their respective institutions of study. At the same time, the campaign hoped that youths would carry these habits over into other dining situations.